Performance Validation of the Microbiologique MicrofilmTM Test System for AOAC Research Institute Performance Tested MethodSM Certification. (23rd November 2019) - Mai, Tam L; Sung, Shao-Lei; Shapovalova, Anna; Janagama, Harish K; Vuong, Long; Friedrich, Alex; Johnson, Dylan; Nadala, Lourdes M; Nguyen, Van; Nadala, Elpidio Cesar; Samadpour, Mansour
Abstract: The Microfilm™ Test System is intended for quantitative microbiology and consists of three types of Microfilms for aerobic plate count (Microfilm APC), total coliform and Escherichia coli count (Microfilm TCEc), and yeast and mold count (Microfilm YMC). This study evaluated the performance of the Microfilm Test System against International Organization for Standardization (ISO) methods on 20 food matrixes and 2 environmental surfaces. Ruggedness, robustness, and stability were also determined, while inclusivity and exclusivity studies were performed on Microfilm TCEc and YMC. An independent laboratory evaluated the performance on four food matrixes and one environmental surface. No significant differences and high correlation coefficients were observed between the Microfilm Test System and the corresponding ISO methods (ISO 4833-1:2013 for APC, ISO 4832:2006 for total coliform count, ISO 16649-2: 2001 for E. coli, and ISO 21527 Part 1 and Part 2 for YMC) in spiked food matrixes and environmental samples. These results were corroborated by the independent laboratory. Inclusivity and exclusivity studies for Microfilm TCEc showed expected results for all the E. coli strains tested (blue-violet or violet color), while the related coliforms showed the expected blue-green colonies on the Microfilm. Similarly, all 100 fungal strains tested showed typical growth on Microfilm YMC. Exclusivity testing on Microfilm TCEc and YMC showed no growth of nontarget organisms. Robustness and ruggedness studies showed no significant differences in mean difference counts at varying incubation temperatures and times. Stability studies on three lots of the Microfilm Test System showed that it is stable at 2–25°C for 12 months and at 45°C for 6 weeks.